Defining empathy: Interconnected discourses of virtual reality's prosocial impact. (August 2021) - Foxman, Maxwell; Markowitz, David M; Davis, Donna Z
While a consumer revolution in virtual reality (VR) has piqued the interest of many fields, industries, and professions, it is unclear when, how, and to what degree the technology can elicit empathy. To better understand how the relationship between VR and empathy is communicated and defined, we performed qualitative and quantitative thematic analyses on popular ( N  = 640) and academic articles ( N  = 53) that included both terms. Findings revealed empathy is an aspirational term for journalists and researchers to showcase the potential of immersive media for prosocial change. Writers in both corpora suggested that empathetic experiences could lead to prosocial action through VR, but do not consistently define or measure empathy, given the inherent complexities surrounding the term. Drawing on seminal research in the field, we conclude with a definition of empathy related to immersive media.